Asymptotic analysis of flow processes at drawing of single optical microfibres - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (International Journal of Chemical Reactor Engineering, 2011)
Microstructured optical fibres (i.e. fibres that contain holes) have assumed a high profile in recent years, and given rise to many novel optical devices. The problem of manufacturing such fibres by heating and then drawing a preform is considered for both the cases of annular microfibres and annular capillaries. A fluid-mechanics model suggested in literature that uses asymptotic analysis based on the small aspect ratio of capillaries is analysed and revised. The leading-order equations are examined in some asymptotic limits, many of which give valuable practical information about the control parameters that influence the drawing process. Additionally, the solution obtained for a single capillary provides a suitable basis for describing more complicated fibre structures. Copyright © 2011 The Berkeley Electronic Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.asympt
Keywords: asymptotic analysis; holey fibre; microstructured optical fibres; numerical efforts; photonic crystal fibres